Terrorist attacks, land resource competition and violent farmer-herder conflicts. (March 2021) - George, Justin; Adelaja, Adesoji; Awokuse, Titus; Vaughan, Olufemi
Highlights: We investigate how armed conflicts relate to farmer-herder conflicts via land use in Nigeria. VAR and Spatial VAR models are employed to explore temporal and spatial relationships. Results suggest terrorism Granger-cause the farmer-herder conflicts, not in reverse. Spatial dependence within conflict types are confirmed. Abstract: Armed conflicts that involve the capture of land and territory can have direct and spillover effects on other land-related conflicts. In this paper, we conceptualize how attacks by terrorists relate to violence from farmer-herder conflicts when both activities are observed in the same geographic area and in the same timeframe. Using both monthly national time series and state-year panel data for Nigeria, we employ Vector Autoregression (VAR) and Spatial VAR (SpVAR) models to examine the existence and direction of temporal and spatial relationships between Boko Haram attacks and violent farmer-herder conflicts. Our VAR results suggest that the former Granger-cause the latter, but not the other way around, supporting the notion that terrorist violence has spillover effects via an increase in violent farmer-herder conflicts. However, our SpVAR results suggest spatial competition or crowding-out between one form of violence and another in a given geographical area. Specific land management and policy implications are also highlighted.